Cross Country Demand and Savings Patterns: An Application of the Extended Linear Expenditure System - Lluch, C.; Williams, R. (The Review of Economics and Statistics, 1975)
C. Lluch, R. Williams, Cross Country Demand and Savings Patterns: An Application of the Extended Linear Expenditure System, The Review of Economics and Statistics, Vol. 57, No. 3 (Aug., 1975), pp. 320-328